2021
DOI: 10.32584/jikm.v4i1.752
|View full text |Cite
|
Sign up to set email alerts
|

Metode Speos (Stimulasi Pijat Endorphin, Oksitosin, Dan Sugestif) Dalam Meningkatkan Produksi Asi Ibu Post Partum

Abstract: Background: Breast milk is the best food that babies need in the first 6 months of life. The success of exclusive breastfeeding is determined at the beginning of offering ASI on the first day of birth. Exclusive breastfeeding can be constrained by the limited production of breast milk. The SPEOS methods is an alternative to help increase breastfeeding. The SPEOS (Endorphin, Oxytocin, and Suggestive Massage Stimulation) methods is a combination of endorpine, oxytocin, and suggestive massage stimulation carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…8 The results of multivariate analysis were to control for confounding variables that could affect milk production in this study age, IMD and maternal nutrition with the result that age and maternal nutrition were not factors that influenced milk production, while IMD had an effect on milk production by 0.375 meaning that IMD provides opportunities affect milk production 37.5% while the rest is influenced by other factors such as fatigue, psychological factors (sobriety and others) which were not examined in this study. 5 According to Diah Eka (2017), that IMD Breastfeeding Initiation) is an action that is carried out by placing the baby immediately after birth with the aim that the baby can find the nipple, this nipple stimulation will stimulate the release of the hormone oxytocin which functions to contract the uterus for release and is the first step in nipple stimulation to secrete colostrum which can facilitate milk production in the first days of the baby's birth, IMD is a strong settler factor for successful breastfeeding. 8 Melyansari's research (2018) shows that the SPEOS method can be a non-pharmacological alternative to increase milk production and overcome problems in breastfeeding, especially in the first days of birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The results of multivariate analysis were to control for confounding variables that could affect milk production in this study age, IMD and maternal nutrition with the result that age and maternal nutrition were not factors that influenced milk production, while IMD had an effect on milk production by 0.375 meaning that IMD provides opportunities affect milk production 37.5% while the rest is influenced by other factors such as fatigue, psychological factors (sobriety and others) which were not examined in this study. 5 According to Diah Eka (2017), that IMD Breastfeeding Initiation) is an action that is carried out by placing the baby immediately after birth with the aim that the baby can find the nipple, this nipple stimulation will stimulate the release of the hormone oxytocin which functions to contract the uterus for release and is the first step in nipple stimulation to secrete colostrum which can facilitate milk production in the first days of the baby's birth, IMD is a strong settler factor for successful breastfeeding. 8 Melyansari's research (2018) shows that the SPEOS method can be a non-pharmacological alternative to increase milk production and overcome problems in breastfeeding, especially in the first days of birth.…”
Section: Discussionmentioning
confidence: 99%
“…The SPEOS method is not only focused on physical conditions but also psychological conditions to increase milk production. 5 Likewise, according to research by Lestari, et al (2019), which used a control group in postpartum mothers who were carried out by the SPEOS method for 4 weeks, it showed that the SPEOS method could be an intervention to increase milk production. In addition to increasing milk production, the SPEOS method has the advantage of being able to do it early on because it has a good impact on accelerating the time for milk release and provides confidence and comfort for postpartum mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penyebab rendahnya cakupan ASI ekslusif selama 6 bulan pertama kehidupan bayi disebabkan salah satunya adalah ibu yang kurang percaya diri bahwa ASI yang dimiliki dapat mencakupi kebutuhan nutrisinya dan masalah yang sering terjadi dihadapi ibu postpartum adalah sedikitnya ASI yang keluar dan bahkan ASI tidak keluar sehingga menyebabkan ketidakberhasilan dalam pemberian ASI ekslusif dan ibu harus memberikan susu formula pada bayinya (Sukriana, 2018). Penyebab proses produksi ASI tidak lancar juga dapat dipengaruhi oleh beberapa faktor, salah satu diantaranya adalah ibu yang mengalami stress, sehingga mengakibatkan terjadinya blokade dari refleks letdown yang diakibatkan karena adanya pelepasan adrenalin (epinefrin) sehingga menyebabkan vasokontriksi pembuluh darah alveoli sehingga menghambat oksitosin untuk mencapai target miopitelium (Arsi., Rejeki & Zulfa., 2021).…”
Section: Pendahuluanunclassified